JURIDICAL ANALYSIS OF DISCIPLINE ENFORCEMENT STATE CIVIL APPARATUS WITHIN THE BATAM CITY GOVERNMENT - Erniyanti Erniyanti; Heri Mardiantika (Badan Penerbit STIEPARI Press, 2023)
State Civil Apparatus (SCA) as state and public servants have a vital role in government. Every State Civil Servant must apply absolute discipline as a public servant. This research aims to determine the implementation of disciplinary enforcement of State Civil Apparatus within the Batam City Government. This research uses qualitative research. This research method is empirical normative research. Empirical normative legal research examines the factual implementation or implementation of favorable legal provisions and contracts in each specific legal event. So, this research requires primary data and secondary data. Data sources were obtained from primary, secondary, and tertiary legal materials. The research results show that enforcement of state civil servant discipline is based on Government Regulation 94 of 2021 concerning Civil Servant Discipline. There are still disciplinary violations committed by the State Civil Apparatus within the Batam City Government. The obstacles faced in enforcing discipline are caused by five factors, namely legal factors themselves, law enforcement factors, advice and infrastructure factors, community factors, and cultural factors. The solution for enforcing discipline from legal factors is that the government immediately issues government regulations regarding the management of salaries and allowances. Law enforcement factors with an increase in the role and function of leadership. Facilities and supporting facilities factors by improving facilities and infrastructure. The societal factor is making dreams a role model and role model for their subordinates. Cultural factors by increasing SCA awareness and understanding of the importance of discipline.